The Influence of Career Development, Motivation, and Work Environment on Job Satisfaction (A Study on Health Workers at Islamic Hospital) - Raji Saputra; Purnadi Purnadi; Alfato Yusnar Kharismasyah; Irawan Randikaparsa (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The primary objective of this research is to examine how career growth, employee motivation, and workplace environment impact job contentment amongst healthcare professionals at the Islamic Hospital of Banjarnegara. This study utilised a quantitative methodology, with a target group of 200 medical staff at the hospital. The selection method employed was purposive sampling based on specific standards, resulting in a sample size of 133 respondents determined using the Slovin formula with a 5% margin of error. Information was gathered through surveys, with each variable assessed using a five-point Likert scale and examined using the Structural Equation Modelling Partial Least Squares (SEM-PLS) technique. The outcomes indicate that career advancement and work conditions have a favourable and meaningful influence on job satisfaction, while motivation does not exhibit a significant impact. These results validate Herzberg's dual-factor theory, highlighting the importance of both motivational and hygiene elements in improving job satisfaction. Therefore, management is expected to pay attention to career development and workplace conditions to help improve employee job satisfaction. This study also recommends a thorough evaluation of motivation programmes to make them more effective.